2021
DOI: 10.1109/access.2021.3110371
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Long-Range Air Traffic Flow Management for the Asia-Pacific Region

Abstract: We provide a concept of operations and a corresponding implementation of a long-range air traffic flow management in the Asia-Pacific region. This management will provide an appropriate demandcapacity balancing considering both aircraft sequencing by local arrival management procedures and flow optimization to prevent over-demand in the approach area around the airport. Thus, coordination of longrange international flights demands collaboration between different flight information regions and local regulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…For balancing the local hotspot deconfliction in the wider regional network, the other potential solution could be strategic arrival traffic flow management. The authors' past research indicated that aircraft arrival time control led to a less severe phase of excessive traffic demands when applying the concept of long range air traffic flow management (LR-ATFM) [25]. The LR-ATFM concept aimed to control the entry time of long-haul flights into the approach sector, assuming the opportunities for aircraft to control speed and/or to change tracks.…”
Section: Collaboration With Long Range Air Traffic Flow Managementmentioning
confidence: 99%
“…For balancing the local hotspot deconfliction in the wider regional network, the other potential solution could be strategic arrival traffic flow management. The authors' past research indicated that aircraft arrival time control led to a less severe phase of excessive traffic demands when applying the concept of long range air traffic flow management (LR-ATFM) [25]. The LR-ATFM concept aimed to control the entry time of long-haul flights into the approach sector, assuming the opportunities for aircraft to control speed and/or to change tracks.…”
Section: Collaboration With Long Range Air Traffic Flow Managementmentioning
confidence: 99%